1999
DOI: 10.1017/s1355838299981359
|View full text |Cite
|
Sign up to set email alerts
|

Nonsense mutations in the alcohol dehydrogenase gene of Drosophila melanogaster correlate with an abnormal 3′ end processing of the corresponding pre-mRNA

Abstract: From bacteria to mammals, mutations that generate premature termination codons have been shown to result in the reduction in the abundance of the corresponding mRNA. In mammalian cells, more often than not, the reduction happens while the RNA is still associated with the nucleus. Here, it is reported that mutations in the alcohol dehydrogenase gene (Adh) of Drosophila melanogaster that generate premature termination codons lead to reduced levels of cytoplasmic and nuclear mRNA. Unexpectedly, it has been found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 39 publications
1
37
0
Order By: Relevance
“…The Adh fn6 allele has a mutation with a sequence repeat and deletion that prevents the splicing of the first intron and leads to a premature stop codon (Benyajati et al 1983). As in Adh n4 flies, the level of Adh fn6 mRNA is drastically reduced (Brogna 1999 (Figure 3). We conclude from the above results that dSmg1 rst1 and dSmg1 rst2 do not abolish NMD even though they almost certainly knock out the ortholog of one of the key players in C. elegans and human NMD.…”
Section: N Onsense-mediated Decay (Nmd) Is An Mrnamentioning
confidence: 81%
See 1 more Smart Citation
“…The Adh fn6 allele has a mutation with a sequence repeat and deletion that prevents the splicing of the first intron and leads to a premature stop codon (Benyajati et al 1983). As in Adh n4 flies, the level of Adh fn6 mRNA is drastically reduced (Brogna 1999 (Figure 3). We conclude from the above results that dSmg1 rst1 and dSmg1 rst2 do not abolish NMD even though they almost certainly knock out the ortholog of one of the key players in C. elegans and human NMD.…”
Section: N Onsense-mediated Decay (Nmd) Is An Mrnamentioning
confidence: 81%
“…To address whether the differentially regulated transcripts were a result of disruption in NMD, we examined transcripts that would be degraded by NMD if they were in mammals (Nagy and Maquat 1998 : To test more directly the role CG32743 plays in NMD in Drosophila, we measured the effect that the dSmg1 rst1 and dSmg1 rst2 mutations had on the abundance of specific transcripts thought to be degraded by NMD. The Adh n4 allele contains a premature stop codon located 258 bp upstream from the boundary between exon 3 and exon 4 and Northern data show that it has 7% of the steady-state mRNA of the wild-type allele (Brogna 1999), presumably due to the action of NMD. Adh n4 males were crossed with dSmg1 rst1 females and the Adh mRNA levels of F 1 offspring were measured.…”
Section: N Onsense-mediated Decay (Nmd) Is An Mrnamentioning
confidence: 99%
“…In addition, other observations in mammalian systems have shown that a PTC can affect specific nuclear events, such as alternative splicing and 3 end formation (Brogna 1999;Wang et al 2002). Muhlemann and colleagues (2001) further demonstrated by fluorescent in situ hybridization (FISH) that pre-mRNAs accumulate in larger transcriptionsite foci from integrated PTC-containing reporter genes, although this interpretation has been recently questioned as being due to NMD-independent events (Lytle and Steitz 2004).…”
Section: Introductionmentioning
confidence: 99%
“…To characterize the role of Drosophila Smg6 in NMD, we analyzed mRNA levels of the well-characterized NMD target gene Adh n4 , which contains a nonsense mutation (Chia et al 1987;Brogna 1999). Adh n4 has been shown to be a bona fide NMD target in both cell culture and whole animals (Brogna 1999;Gatfield et al 2003;Chen et al 2005;Metzstein and Krasnow 2006).…”
Section: Third Chromosome Screen Has Isolated First Drosophila Allelementioning
confidence: 99%
“…Adh n4 has been shown to be a bona fide NMD target in both cell culture and whole animals (Brogna 1999;Gatfield et al 2003;Chen et al 2005;Metzstein and Krasnow 2006). Furthermore, Adh is expressed in most, if not all Drosophila tissues (Chintapalli et al 2007), so by analyzing this gene we can assess the role played by NMD in diverse cell types.…”
Section: Third Chromosome Screen Has Isolated First Drosophila Allelementioning
confidence: 99%